Balloon-assisted percutaneous thrombin injection in a subclavian artery pseudoaneurysm: A case report - Nouf Alghaith; Abdulrahman Algain; Abdulqader Alkenawi; Salman Felemban (Radiology Case Reports)
Subclavian artery pseudoaneurysm (SAP) is a rare but lethal diagnosis, and an important condition that should be detected and managed imperatively. SAP has been seldom described in the literature, explaining the lack of concrete management guidelines. Herein we present a case study of a 63-year-old man with SAP post a transcatheter aortic valve implantation (TAVI) done 8 days prior to current presentation. Our case highlights the importance of imaging in early detection and ultimately the management of such complication. Also, proves the efficacy and safety of thrombin injection in the treatment of SAP.